Avaliação da corrosividade e estabilidade oxidativa de biodiesel em condições simuladas de armazenamento - Moura, Dalyelli de Souza Serqueira (2017)
Fatty acid methyl esters (biodiesel) are easily oxidized due to their properties and chemical composition. The degradation reactions are related to several factors, among them the carbonic chain structure of these esters and the presence of metallic ions. This thesis aimed to evaluate the corrosiveness and oxidation stability of two biodiesel (soybean methyl biodiesel – BMS and recycled cooking oil methyl biodiesel - BMR), under simulated storage conditions in absence and presence of the antioxidants tert-butyl-hydroquinone (TBHQ), butylhydroxytoluene (BHT), propylgallate (PG) and curcumin. To simulate such conditions, immersion corrosion tests (ASTM) were performed with the biodiesels, to which were immersed coupons of carbon steel (1020) and copper, materials found in storage tanks and/or inside engines. The analyzed biodiesels were within the Brazilian regulatory agency ANP specifications. The efficiency order of antioxidants differed between the biodiesels, PG>Curcumin>BHT>TBHQ for BMS and PG>BHT>Curcumina>TBHQ for BMR. The properties acid index (IA), peroxide index (IP) and oxidation stability (PI) were measured during the corrosion tests, as well as the corrosion rate. The IA values did not vary significantly during the 84 days of experiment, with or without antioxidants. The efficiency order of the antioxidants during the exposure to carbon steel was the same found for the oxidation stability measurements of both biodiesels. The corrosion rate diminished during the corrosion test, which indicated blockage of the metallic surface by oxidation products or antioxidants. Copper was more susceptible to corrosion by biodiesel, with a corrosion rate of 1.263 mpy, while carbon steel, under the same conditions, presented the value of 0.129 mpy. Therefore, it can be concluded that antioxidants, in a similar way, acted as corrosion inhibitors in all tests, with higher efficiency to PG, and it was found a direct correlation between oxidation stability and efficiency in corrosion inhibition.